ANALISIS HUKUM TERHADAP STANDARISASI LINGKUNGAN DALAM PERDAGANGAN INTERNASIONAL (ECOLABELL) - Riadhi Alhayyan; Syamsul Arifin; Jelly Leviza; Mahmul Siregar (USU LAW JOURNAL, 2015)
ABSTRACT Environmental standards important to get the attention of the national legal system . Legal arrangement of standardization environment ( eco-labeling ) is not specifically fit but still refers to the standardization of the environment that the fit within the framework of WTO agreements that have been ratified in Law No. 7 of 1994 in this case related to the environmental aspects of the Agreement on Technical barriers to Trade and the agreement on the Application of Sanitary and Phytosanitary Measures ( SPS ). Standardization of the environment within the framework of WTO trade agreements in the context of his position, the main purpose of the GATT / WTO is free trade. GATT / WTO is not an environmental protection agency and does not have a mandate on the environment, only in this case to prevent barriers to trade (TBT), which can lead to the dreaded proteknisme and trade discrimination, the WTO stipulates that environmental aspects should be included in the terms of trade, but of competence for coordination policy in this field is restricted trade policies, and therefore the framework of WTO trade agreement is not the proper forum to resolve environmental problems due to shortage of neutrality of this institution to balance trade and environmental policy. Standardize the application of WTO environment in an atmosphere of national law as it has been ratified by the Indonesian government with Law No. 7 of 1994 regarding TBT especially concerning standardization in member countries to reiterate that in this case Indonesia was required to adjust the rules and regulations perudang national regulation in the field of standardization. This agreement recognizes that the Member States in this regard should not be prevented Indonesia issued a regulation and establishes a minimum standard level to safeguard and environmental management in its application should not be any element of discrimination and should not create unnecessary obstacles to trade. Indonesia currently has Ekolable Indonesian Institute which is based on a single commitment that the sustainability of the environment. Keywords : Standardization , the environment , international trade